The Monday effect and the Johannesburg Stock Exchange: Revisited - Sinclair Davidson; Steven Meyer (South African Journal of Business Management, 1993)
The Monday effect is an anomaly that has defied explanation. It has been found to be present in major stock exchanges around the world. Bhana found evidence in favour of this anomaly in the share returns on the Johannesburg Stock Exchange (JSE). In this article the Monday effect on the JSE is reinvestigated in a later period. The methodology employed is superior to that of previous studies. It appears that the Monday effect is no longer present in the pattern of share returns on the JSE. The results of the article suggest that the original methodology creates a bias in favour of finding a Monday effect. Evidence in favour of the trading time hypothesis is found, indicating that no equity growth occurs over weekends.
Keywords: 650